Digitality in ethics learning units - Dörfer, Claudia; Madrigal Lozano, María Magdalena; Ulloa Duque, Gabriela Soledad; Osorio Calderón, Jesús (2020)
This study constructed and validated an attitude scale for ethics learning units using technology among undergraduate students in a Mexican business school. We sought to determine whether the motivation and usage of a learning-management system (LMS) combined with learning elements in mobile applications and the active support of instructor increases motivation, willingness to learn, learning benefit, and satisfaction in ethics learning units. The approach of this study is quantitative, transversal, and not experimental and used a sample (N = 227) of international business, administration, and public accounting undergraduate students. The self-reported data from students were obtained from anonymous questionnaire surveys. It is a pilot study and the sample presented is relatively small, which limits the applicability of the findings. Because the instrument is a self-support and is anonymous, participants can respond in socially desirable terms, remaining neutral in the response.